Meningkatkan Pemahaman Meningkatkan Pemahaman Siswa SMK Muhammadiyah 2 Kota Tangerang Selatan Pentingya Kemampuan Bermatematika Jika Ingin Melanjutkan Pendidikan Tinggi di Bidang Teknik - Perak Samosir; Yenny Widyanti; Ratnawati; Gadih Ranti (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2026)
Higher education in engineering is one of the most popular and sought-after majors among high school (SMA) and equivalent students such as vocational schools (SMK). Engineering majors are considered to offer good, bright, and promising prospects, including the availability of extensive job opportunities, especially in the industrial and construction sectors. However, the path to achieving this requires students to have good mathematical skills, which must be started at the latest when students are in high school/vocational school. The Community Service (PKM) activity that we conducted tried to find out how the tenth grade students of SMK Muhammadiyah 2 South Tangerang City view the subject of Mathematics. Of the 39 students, only 2 students said they liked Mathematics and 37 people gave answers that gave the impression that Mathematics is difficult and confusing. In this PKM activity, we gave 2 presentations that illustrated how Mathematics is needed in everyday life. At the end of the activity, a question and answer session was held and through the questions asked by the students, it was seen that the students gave a positive response to this activity.